Detecting vulnerable carotid plaque and its component characteristics: Progress in related imaging techniques - Weng, Shi-Ting; Lai, Qi-Lun; Cai, Meng-Ting; Wang, Jun-Jun; Zhuang, Li-Ying; Cheng, Lin; Mo, Ye-Jia; Liu, Lu; Zhang, Yin-Xi; Qiao, Song (Frontiers in Neurology, 2022)
Carotid atherosclerotic plaque rupture and thrombosis are independent risk factors for acute ischemic cerebrovascular disease. Timely identification of vulnerable plaque can help prevent stroke and provide evidence for clinical treatment. Advanced invasive and non-invasive imaging modalities such as computed tomography, magnetic resonance imaging, intravascular ultrasound, optical coherence tomography, and near-infrared spectroscopy can be employed to image and classify carotid atherosclerotic plaques to provide clinically relevant predictors used for patient risk stratification. This study compares existing clinical imaging methods, and the advantages and limitations of different imaging techniques for identifying vulnerable carotid plaque are reviewed to effectively prevent and treat cerebrovascular diseases.